2022
DOI: 10.1038/s41467-022-32601-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution and strain generation of derived-Cu catalysts during CO2 electroreduction

Abstract: Copper (Cu)-based catalysts generally exhibit high C2+ selectivity during the electrochemical CO2 reduction reaction (CO2RR). However, the origin of this selectivity and the influence of catalyst precursors on it are not fully understood. We combine operando X-ray diffraction and operando Raman spectroscopy to monitor the structural and compositional evolution of three Cu precursors during the CO2RR. The results indicate that despite different kinetics, all three precursors are completely reduced to Cu(0) with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 64 publications
1
55
1
Order By: Relevance
“…The higher metallic Cu proportion of transformed HIF compared to LIF indicates a more significant reduction on HIF during the dynamic evolution. Although some previous works reported that Cu oxides would be totally reduce to metallic Cu quickly under EC CO 2 RR conditions, [34] our operando result boldly evidenced that Cu 2 O remain existed in both LIF and HIF during 4 cycle runs.…”
Section: Tracking the Initial Exposed Facet Induced Reconstructioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The higher metallic Cu proportion of transformed HIF compared to LIF indicates a more significant reduction on HIF during the dynamic evolution. Although some previous works reported that Cu oxides would be totally reduce to metallic Cu quickly under EC CO 2 RR conditions, [34] our operando result boldly evidenced that Cu 2 O remain existed in both LIF and HIF during 4 cycle runs.…”
Section: Tracking the Initial Exposed Facet Induced Reconstructioncontrasting
confidence: 54%
“…The full width at half maximum (FWHM) of the diffraction peak is indicative of the crystal size according to Scherrer equation (Equation S1, Supporting Information), where the mean size of the ordered crystalline domains was inversely proportional to FWHM. [ 34 ] As summarized in Figure 5b, the FWHM of Cu 2 O (200) was 0.026° for fresh LIF and this small value (< 0.1 degree) was kept in the following reaction cycles, while the FWHM of Cu (111) was much larger than that of Cu 2 O (200). Therefore, Cu 2 O phase in LIF maintained a relatively larger size (micro particles), while the Cu particles evolved from the constrained environment of the oxide lattice existed in nanometric scale.…”
Section: Resultsmentioning
confidence: 98%
“…This possibility is supported by the idea of presence of undercoordinated Cu metals in NCDC. As per the discussion in the Introduction section and recent disclosure of operando analyses, these Cu 0 take part in the effective reduction of those hydrogen ions to H 2 gas. Moreover, the surface oxidized Cu precursors are expected to reduce to Cu(0) when delivering their maximum FE for H 2 O reduction; however, they will be again oxidized in ambient condition due to high surface energy of the nanoparticles. This kind of efficient reduction is only possible when the surface-active sites are mostly covered (higher θ). , …”
Section: Resultsmentioning
confidence: 98%
“…The exposed copper is expected to oxidize (Cu 2+ ) because of the high surface energy and dangling bond of the surface atoms. Notably, recent structural and compositional operando analyses of Cu 2+ -based catalysts during CO 2 reduction reaction revealed that the oxidized Cu precursors are all completely reduced to Cu(0) when delivering their maximum Faradaic efficiencies (FE) for CO 2 reduction. Therefore, we also expect a similar situation in the alkaline water reduction reaction at the cathode by the undercoordinated surface Cu 2+ for moderate adsorption–desorption affinity of hydrogen adsorbed (H ads ) after the selective leaching of NiCu alloy. , This will particularly enhance the dissociation of water molecule and the prevention from hydroxyl adsorption (OH ads ), which we proved by combined experimental and density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 97%
“…The lingering mystery on the structure–reactivity relationship is mainly caused by the complex and variable nature of Cu-based materials . A significant challenge is that the Cu-based catalysts undergo a reconstruction process under the reaction conditions, such as the trend of separating out of oxygen from Cu oxides at negative potentials, which renders the understanding of the origin of the improved CO 2 RR performance and thus the theory of rational catalyst design difficult. Therefore, it is of great significance to explore the dynamic evolution process and the in situ reconstructed active sites for electrocatalysis under the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%